2010
DOI: 10.1073/pnas.1001360107
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hypertrophy is not amplified by deletion of cGMP-dependent protein kinase I in cardiomyocytes

Abstract: It has been suggested that cGMP kinase I (cGKI) dampens cardiac hypertrophy. We have compared the effect of isoproterenol (ISO) and transverse aortic constriction (TAC) on hypertrophy in WT [control (CTR)] mice, total cGKI-KO mice, and cGKIβ rescue mice (βRM) lacking cGKI specifically in cardiomyocytes (CMs). Infusion of ISO did not change the expression of cGKI in the hearts of CTR mice or βRM but raised the heart weight by ∼20% in both. An identical hypertrophic growth response was measured in CMs from CTR m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
137
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(149 citation statements)
references
References 62 publications
10
137
0
2
Order By: Relevance
“…1D). This result suggests, in agreement with our previous findings (22), that the absence of cGKI in the CMs and ECs of the heart does not increase the extent of cardiac hypertrophy, at least under normal physiological conditions.…”
Section: Aii Induces Cardiac Hypertrophy In the Absence And Presence Ofsupporting
confidence: 82%
See 3 more Smart Citations
“…1D). This result suggests, in agreement with our previous findings (22), that the absence of cGKI in the CMs and ECs of the heart does not increase the extent of cardiac hypertrophy, at least under normal physiological conditions.…”
Section: Aii Induces Cardiac Hypertrophy In the Absence And Presence Ofsupporting
confidence: 82%
“…This result strongly suggests the major effects of sildenafil on these parameters are due to effects outside of the SMCs and CMFs. (iv) Similarly to what has been observed with isoproterenol infusion and aortic constriction (22), AII-induced hypertrophy was not augmented and, if anything, slightly reduced in βRM compared with WT mice despite an increase in fibrosis (Fig. 4).…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Binding of NO to the heme of GC1 increases the catalytic activity >50‐fold. The NO‐GC1‐cGMP pathway regulates numerous cardiovascular functions, including vascular tone and cardiac homeostasis, mostly through activation of protein kinase G. Specifically in the heart, the NO‐cGMP signaling has a well‐established cardioprotective effect against hypertrophy, acute ischemia/reperfusion injury, and heart failure 1. In isolated cardiomyocytes from systemic GCα1 knockout (GCα1‐KO) mice, a model used herein, it was shown that GC1 modulates cardiac contractility by mediating both negative and positive ionotropic effects, under β3 adrenergic stimulation and basal condition, respectively 2.…”
mentioning
confidence: 99%